2019
DOI: 10.3390/su11071900
|View full text |Cite
|
Sign up to set email alerts
|

Inclusive Financial Development and Multidimensional Poverty Reduction: An Empirical Assessment from Rural China

Abstract: Inclusive finance is often considered to be a critical element that makes growth inclusive, as access to finance can enable the poor to lift themselves from income poverty. However, can it play such a role when the poor are in multidimensional poverty? Why does financial exclusion and poverty still exist in countries with vigorous development of inclusive finance? We build an evolutionary game model to analyze the equilibrium strategies of inclusive financial institutions and the poor in poverty reduction acti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(19 citation statements)
references
References 18 publications
(30 reference statements)
0
10
0
Order By: Relevance
“…Li et al used the two-player EGM to simulate the performance of supply chain members under the environment of financial risk [39]. Yang and Fu constructed an EGM to analyse the equilibrium strategies of inclusive financial institutions and the poor in poverty-reduction activities [40]. Liu and Xia constructed an EGM between borrowers and lenders in P2P lending market to study the impact of evolutionary equilibrium strategies of lenders and borrowers' behavioural strategies on the risk to the P2P lending platforms under bounded rationality [20].…”
Section: Related Workmentioning
confidence: 99%
See 1 more Smart Citation
“…Li et al used the two-player EGM to simulate the performance of supply chain members under the environment of financial risk [39]. Yang and Fu constructed an EGM to analyse the equilibrium strategies of inclusive financial institutions and the poor in poverty-reduction activities [40]. Liu and Xia constructed an EGM between borrowers and lenders in P2P lending market to study the impact of evolutionary equilibrium strategies of lenders and borrowers' behavioural strategies on the risk to the P2P lending platforms under bounded rationality [20].…”
Section: Related Workmentioning
confidence: 99%
“…us, it is necessary to understand the interest and interactions of P2P lending participants to coordinate the interest among them for achieving sustainable development of the P2P lending industry. (3) According to the aforementioned literature, the EGM of two game groups or two players is often applied in studies [20,[36][37][38][39][40]. However, practical cases usually involve more than two participants.…”
Section: Related Workmentioning
confidence: 99%
“…In addition, it was found that the urban–rural income gap had a significant, negative impact on the digital financial inclusion index. Using data related to digital financial inclusion and poverty relief from 31 provinces, autonomous regions and municipalities in China from 2011 to 2015, Yang (2019) found that digital support services and inclusive credit services had a positive effect on poverty-alleviation efficiency in rural areas. However, the effect of digital financial inclusion on poverty alleviation was observed to vary significantly between rural and urban areas (Yang, 2019).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Using data related to digital financial inclusion and poverty relief from 31 provinces, autonomous regions and municipalities in China from 2011 to 2015, Yang (2019) found that digital support services and inclusive credit services had a positive effect on poverty-alleviation efficiency in rural areas. However, the effect of digital financial inclusion on poverty alleviation was observed to vary significantly between rural and urban areas (Yang, 2019). The author found that information infrastructure and the development of the financial service industry were key factors affecting poverty-alleviation efficiency.…”
Section: Literature Reviewmentioning
confidence: 99%
“…After eliminating absolute poverty, the problem of relative poverty in China remains severe and will remain for a long time to come. How to consolidate the achievements of poverty eradication and increase the income of rural residents has become an important issue facing the all-round construction of a great modern socialist country [3]. A good rural financial ecological environment can promote the efficient operation of rural finance.…”
Section: Introductionmentioning
confidence: 99%